Auditoría de la seguridad informática a la empresa Markglob de la ciudad de Machala. - Caminos Cuenca, Sandra Yuliana (My University, 2019)
In the knowledge society the management of information and data management is vital in any company or institution, with the aim of automating sequential processes, improving the performance of systems and integrating software tools in the execution of tasks, contributing to achieve competitiveness in an increasingly demanding and volatile market. The computer audit is an interdisciplinary and intrinsic science that brings together all the departments and involved in an organization, evaluating security, computational processes and quality of information to guarantee a correct performance minimizing the risks at a profitable cost. The company MarkGlob is an entity dedicated to carrying out market studies and advertising strategies in the city of Machala, using multiple digital resources and information in its work; For this reason, the aim of this study is to identify the measures / controls carried out by maintaining the security of its facilities, to explain how it harmonizes risks / information potentialities.
En la sociedad del conocimiento el manejo de la información y gestión de datos es vital en toda empresa o institución, con el objeto de automatizar procesos secuenciales, mejorar las prestaciones en sistemas e integrar herramientas de software en la ejecución de tareas, contribuyendo a lograr la competitividad en un mercado cada vez más exigente y volátil. La auditoría informática es una ciencia interdisciplinaria que conjuga a todos los departamentos involucrados en una organización, evaluando la seguridad, procesos computacionales y calidad de la información para garantizar un correcto desempeño minimizando los riesgos a un costo rentable. La empresa MarkGlob es una entidad dedicada a realizar estudios de mercado y estrategias publicitarias en la ciudad de Machala, emplea múltiples recursos digitales e información en sus labores; por ello en este estudio se pretende identificar las medidas/controles que realiza al mantener la seguridad en sus instalaciones, explicar la manera en que armoniza los riesgos/potencialidades informáticas.
Keywords: AUDITORIA INFORMÁTICA; SEGURIDAD; CONTROLES; EMPRESA; PUBLICIDAD